Electricity Law No.87/2015 = قانون الكهرباء رقم 87 لسنة 2015 / Prime Minister. - Egypt. Prime Minister. (2025)
Decree of the President of the Arab Republic of Egypt by law no. 87 of the year 2015 issuing the electricity law – قرار رئيس جمهورية مصر العربية بالقانون رقم 87 لسنة 2015 بإصدار قانون الكهرباء 1. Definitions -- 2. The organization of the electric utility -- 3. The electricity activities -- 4. Improving the efficiency of energy use -- 5. Electric utility facilities -- 6. The transitional period and the competitive electricity market -- 7. The penalties -- 8. Final provisions.